Dominance‐function relationships in the amphibian skin microbiome. (26th July 2017) - Walke, Jenifer B.; Becker, Matthew H.; Hughey, Myra C.; Swartwout, Meredith C.; Jensen, Roderick V.; Belden, Lisa K.
Summary: Some amphibian skin bacteria inhibit growth of a fungal amphibian pathogen, Batrachochytrium dendrobatidis (Bd), but it is unclear how dominant these anti‐Bd bacteria are in skin communities. Using in vitro co‐culture challenge assays, we quantified Bd inhibition by bacterial isolates collected from the skin of four amphibian species: bullfrogs, Eastern newts, spring peepers and American toads. The 16S rRNA sequences for each isolate were matched to culture‐independent amplicon sequences from the same individuals to assess inhibitory function versus relative abundance. Dominant bacteria had higher Bd inhibition than rare bacteria in bullfrog and newt populations, in which Bd was prevalent (> 25%). Dominant and rare bacteria did not differ in Bd inhibition in spring peeper and toad populations, in which Bd was absent or at low prevalence (< 7%). In addition, over half of the relative abundance of cultured bacteria on bullfrogs and newts was comprised of inhibitory bacteria, while only 25% and 37% of the relative abundance was inhibitory on spring peepers and toads, respectively. These results suggest that the dominant members of the amphibian skin bacterial community may be functionally important in terms of disease‐resistance, and that Bd prevalence and/or host species identity may impact the relative abundance and inhibitory properties of skin bacteria.